Micropillar compression response of femtosecond laser-cut single crystal Cu and proton irradiated Cu. (September 2019) - Gigax, Jonathan G.; Vo, Hi; McCulloch, Quinn; Chancey, Matthew; Wang, Yongqiang; Maloy, Stuart A.; Li, Nan; Hosemann, Peter
Abstract: Femtosecond laser cutting has been used to fabricate micro- and mesoscale specimens for mechanical testing, but the impact on mechanical properties has not been fully evaluated. Micropillars of various sizes were fabricated in a single crystal Cu specimen and Cu irradiated to 1.4 peak displacements per atom using a femtosecond laser cutting system followed by focused ion beam milling to a final dimension of 7 μm × 7 μm × 12 μm. Microcompression testing showed that removing 5 μm of material from the laser cut surface in both specimens resulted in similar behavior to purely focused ion beam milled micropillars. Graphical abstract: Unlabelled Image